KONFLIK KEPEMIMPINAN DALAM PEKABARAN INJIL: SEBUAH PEMAKNAAN TERHADAP PERSELISIHAN PAULUS DAN BARNABAS DALAM KISAH PARA RASUL 15:35-41 - Dwi Atni Setyowati (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2019)
This paper discusses a conflict involving Paul and Barnabas in Acts 15:35-41. Stott argued that this conflict is a sad story. Nevertheless, based on the narrative interpretation exploring some narrative components in Acts 15:35-41, namely plot, time and place setting, characters, and narrative rhetoric, this paper is to show that the story of the conflict is not a sad story. Actually, the story is a part of Luke’s rhetoric in exposing that the work of the Holy Spirit was not be able to be resisted by everything and telling about the consequences of different models of leadership especially in recruitment for the sake of God’s mission as well.